Why the Chinese cyber attack is the ultimate scare story. - Miles, Alice (New Statesman, 2011)
The author offers opinions on world politics and journalism. Much reporting in mass media is said to present events as purely symbolic, with the visit of U.S. President Barack Obama to Great Britain cited as an example of news intended to be reassuring to the public. By contrast, reports that a Chinese government agency was engaged in widespread computer hacking is said to be a reflection of the public's limited knowledge of or ability to cope with computer crime.